Reading. Grade 6 connecting school and home - Cheney, Martha; Benton, Jeannette; Kershner, Jack; Palmer, Daniel W; Palmer, Jim (Monterey, CA Evan-Moor Corp, 2005)
Provides at-home practice that helps to boost students' reading skills through engaging stories and activities that support Common Core State Standards. Activities provide practice in reading literature and informational text, and cover the essential components of reading instruction : comprehension, vocabulary, phonics / structural analysis, and fluency. Other literacy topics include grammar, spelling, reference skills, and writing
English Language
1
Keywords: Reading (Elementary); Reading comprehension